State of the art of additive manufacturing: Review for tolerances, mechanical resistance and production costs. Issue 1 (31st December 2016) - Fera, M.; Fruggiero, F.; Lambiase, A.; Macchiaroli, R.
Abstract: The new technology named additive manufacturing (AM) is gaining significance in the industrial sector due to its capacity to define new improvements in the design, production and logistical issues related to a specific product. This new area in industrial engineering is becoming operative but is still not easily applicable to all types of production systems. Many research and practical contributions have been developed in the last few years, but a unique answer for a possibility to be applied to the industrial sector has not yet been derived. This paper aims to analyse existing research literature on AM application in the industrial sector and tries to determine the open issues related to this theme. Here the themes on the mechanical and chemical characteristics of the materials produced with AM and the management theme are examined.